2017
DOI: 10.1128/aem.00207-17
|View full text |Cite
|
Sign up to set email alerts
|

The Conjugative Relaxase TrwC Promotes Integration of Foreign DNA in the Human Genome

Abstract: Bacterial conjugation is a mechanism of horizontal DNA transfer. The relaxase TrwC of the conjugative plasmid R388 cleaves one strand of the transferred DNA at the gene, covalently attaches to it, and leads the single-stranded DNA (ssDNA) into the recipient cell. In addition, TrwC catalyzes site-specific integration of the transferred DNA into its target sequence present in the genome of the recipient bacterium. Here, we report the analysis of the efficiency and specificity of the integrase activity of TrwC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 38 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…These plasmids (pAA58 and pMTX808; Table 2 ) were introduced in B. henselae , and the resulting strains were used to infect both EA.hy926 and HeLa human cell lines. The former is derived from HUVEC cells, which are the natural target of B. henselae in vivo ; however, HeLa cells can also be infected by B. henselae with lower efficiency, and we showed that TrwC-mediated DNA transfer takes place to HeLa cells as well ( Gonzalez-Prieto et al, 2017 ). B. henselae carrying plasmids coding for either MobA or TrwC, or relaxase mutants as negative controls, were used for infections.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These plasmids (pAA58 and pMTX808; Table 2 ) were introduced in B. henselae , and the resulting strains were used to infect both EA.hy926 and HeLa human cell lines. The former is derived from HUVEC cells, which are the natural target of B. henselae in vivo ; however, HeLa cells can also be infected by B. henselae with lower efficiency, and we showed that TrwC-mediated DNA transfer takes place to HeLa cells as well ( Gonzalez-Prieto et al, 2017 ). B. henselae carrying plasmids coding for either MobA or TrwC, or relaxase mutants as negative controls, were used for infections.…”
Section: Resultsmentioning
confidence: 93%
“…The conjugative relaxase TrwC can be translocated through the T4SS VirB/D4 of B. henselae to human cells, where it promotes the integration of the transferred DNA into the recipient genome ( Gonzalez-Prieto et al, 2017 ). In this work, we wanted to test whether this is a unique feature of TrwC and VirB/D4, or other systems can also be combined to deliver and integrate DNA into human cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The translocated DNA is covalently attached to the conjugative relaxase. They showed that certain relaxases promote random integration of the incoming DNA into the recipient human genome (Gonzalez‐Prieto, Gabriel, Dehio, Schmidt, & Llosa, ). Through protein engineering, relaxase chimeric proteins can acquire new functions, including the ability to integrate the attached DNA (Agundez et al, ).…”
Section: Translocated Substratesmentioning
confidence: 99%
“…into the recipient human genome(Gonzalez-Prieto, Gabriel, Dehio, Schmidt, & Llosa, 2017). Through protein engineering, relaxase chime-ric proteins can acquire new functions, including the ability to integrate the attached DNA (Agundez et al, 2018).…”
mentioning
confidence: 99%